2019
DOI: 10.3390/ma12060970
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Porous Dressings Based on Butyric-Acetic Chitin Co-Polymer on Biological Processes In Vitro and In Vivo

Abstract: In spite of intensively conducted research allowing for the development of more and more advanced wound dressing materials, there is still a need for dressings that stimulate not only reparative and regenerative processes, but also have a positive effect on infected and/or difficult-to-heal wounds. Porous dressing materials based on butyric-acetic chitin co-polyester containing 90% of butyryl and 10% of acetyl groups (BAC 90/10) can also be included in the group mentioned above. Two types of dressings were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…The dressing shortens and weakens the exudative phase, drains the wound and accelerates the productive phase. The epithelialization process under the butyryl-acetyl chitin co-polyester was completed faster compared to the control sample [37].…”
Section: Chitin Co-esters In Dressing Materialsmentioning
confidence: 86%
See 1 more Smart Citation
“…The dressing shortens and weakens the exudative phase, drains the wound and accelerates the productive phase. The epithelialization process under the butyryl-acetyl chitin co-polyester was completed faster compared to the control sample [37].…”
Section: Chitin Co-esters In Dressing Materialsmentioning
confidence: 86%
“…It confirmed the sample surface degradation, which was connected to the hydrolysis of ester BAC 90/10 groups. In the in vivo tests, the dressings under macroscopic examination, in full thickness defects of subcutaneous tissue and skin caused wound healing with no inflammation, undergoing the most gradual biodegradation between weeks 4 and 8, and the observed differences were statistically significant [37].…”
Section: Chitin Co-esters In Dressing Materialsmentioning
confidence: 95%
“…For manufacturing of the Medisorb R Membrane and Medisorb R Ag, the method using NaCl as porophor and 3% BAC 90:10 solution in ethanol was applied. The exact manufacturing methods of the dressings and their full physio-chemical and biological characteristics (in vivo and in vitro tests on animals) are presented in other papers [44][45][46].…”
mentioning
confidence: 99%
“…The dressings used within the clinical trials were tested in in vitro conditions where it was demonstrated that the Medisorb R dressings degrade when under the influence of the serum/plasma enzyme and that Medisorb R Ag shows bacteriostatic and bactericidal activity. There were also tests regarding irritation after multiple applications on skin, sensitization activities, healing-in process after intradermal application for up to 6 months, and the influence of the dressing on healing of skin loss of full thickness for up to 21 days [45]. It was concluded that porous Medisorb R and Medisorb R Ag dressings are biocompatible and safe materials.…”
mentioning
confidence: 99%
See 1 more Smart Citation